Credit intermediation and the European internal market for mortgage credit. Issue 1 (2nd January 2019) - Bruloot, Diederik; Callens, Evariest; De Muynck, Michiel
Abstract : The European Mortgage Credit Directive (MCD) aims to create a Union-wide mortgage credit market with a high level of consumer protection. While focussing on the primary policy objective, i.e. facilitating the emergence of an internal market for mortgage credit, this paper analyses the MCD's regulation of the activities of credit intermediaries, and the rules on establishment and supervision of credit intermediaries in particular. As professional middlemen, credit intermediaries could reduce information asymmetries between on the one hand creditors and on the other hand consumers. Against the background of Fintech intermediary disruption and the increasing importance of digital distribution channels for financial services, our paper analyses whether and/or to what extent the MCD's prudential rules for credit intermediation qualify as true "enablers" for an Internal market for mortgage credit.